Parents' Perspectives on Supporting Their Decision Making in Genome‐Wide Sequencing. Issue 3 (7th April 2016) - Li, Karen C.; Birch, Patricia H.; Garrett, Bernard M.; MacPhee, Maura; Adam, Shelin; Friedman, Jan M.
Abstract: Purpose: The purpose of this study was to explore parents' perceptions of their decisional needs when considering genome‐wide sequencing (GWS) for their child. This is a partial report and focuses on how parents prefer to receive education and information to support their decision making about GWS. Design: This study adopted an interpretive description qualitative methodological approach and used the concept of shared decision making and the Ottawa Decision Support Framework. Methods: Participants were parents who had already consented to GWS, and had children with undiagnosed conditions that were suspected to be genetic in origin. Fifteen parents participated in a focus group or individual interview. Transcriptions were analyzed concurrently with data collection, iteratively, and constantly compared to one another. Repeat interviews were conducted with five of the parents to confirm, challenge, or expand on the developing concepts. Findings: Participants felt that their decision to proceed with GWS for their child was an easy one. However, they expressed some unresolved decisional needs, including a lack of knowledge about certain topics that became relevant and important to them later and a need for more support and resources. Participants also had ongoing informational and psychosocial needs after the single clinical encounter where their decision making occurred. Conclusions: Participants expressed unmet decisional needs, which may have influenced the quality of their decisions. The strategies that participants suggested may help create parent‐tailored education, counseling, decision support, and informed consent processes. Clinical Relevance: Health care professionals who offer GWS for children should assess parents' values, priorities, and informational needs and tailor information accordingly. There are opportunities for nurses to become involved in supporting families who are considering GWS for their child.